The Application of the Discovery Learning Model to Improve the Mathematical Problem-Solving Abilities of Eighth Grade Students at SMP Negeri 31 Medan - Simanjuntak, Sinta Dameria; Sinaga, Ewilda; Manurung, Nurhalimah; Capah, Syafwani Sadanta; Harahap, Yanti Pertiwi; Sitanggang, Derma Yanti; Simatupang, Esra Ayu Lamria; Tarigan, Yenni Andryani (International Journal of Trends in Mathematics Education Research, 2024)
This study aims to improve the mathematical problem solving ability of students in class VIII-4 at SMP Negeri 31 Medan through the application of the Discovery Learning model. This research is a Classroom Action Research (PTK) which was conducted in two cycles. The research subjects were 30 students of class VIII-4, while the research object was the improvement of mathematical problem solving ability through Discovery Learning model. The results showed an increase in students' mathematical problem solving skills from cycle I to cycle II. In the initial test, the average student score was 45.22 with a completeness rate of only 13.33%. After the application of Discovery Learning in cycle I, the average score increased to 66 with a completeness rate of 56.67%. In cycle II, the average score reached 82.66 with a completion rate of 86.67%. Thus, the use of the Discovery Learning model proved to be effective in improving students' mathematical problem solving skills on the material of Linear Equation One Variable.